1979
DOI: 10.3758/bf03329396
|View full text |Cite
|
Sign up to set email alerts
|

Methods of deconditioning persisting avoidance: Diazepam as an adjunct to response prevention

Abstract: Rats were trained to avoid footshock during three daily sessions, 100 trials/session, in an automated one-way avoidance chamber. Subsequent to training, footshock was terminated and the rats' persistence in responding was tabulated. Between training and the test of persisting avoidance, three groups of rats received a response prevention (RP) treatment and one group received no RP. RP consisted of forcing the rats to stay on the once-dangerous grid for 5 min, once a day for 4 days. Two groups received RP under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
3
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
3
3
0
Order By: Relevance
“…Importantly, the present behavioral findings extend the existing knowledge about the role of the GABAergic system for extinction learning, which derives from research on fear extinction in rodents (Makkar et al 2010 ). Corresponding to several studies that reported impairment of extinction learning after systemic GABA A agonism (Bouton et al 1990 ; DiSorbo et al 2009 ; Goldman 1977 ; Gorman et al 1979 ; Kamano 1972 ), we can show for the first time that the deficit is not restricted to fear extinction in animals, but also applies to human extinction learning in an associative learning task without a fear component.…”
Section: Discussionsupporting
confidence: 84%
“…Importantly, the present behavioral findings extend the existing knowledge about the role of the GABAergic system for extinction learning, which derives from research on fear extinction in rodents (Makkar et al 2010 ). Corresponding to several studies that reported impairment of extinction learning after systemic GABA A agonism (Bouton et al 1990 ; DiSorbo et al 2009 ; Goldman 1977 ; Gorman et al 1979 ; Kamano 1972 ), we can show for the first time that the deficit is not restricted to fear extinction in animals, but also applies to human extinction learning in an associative learning task without a fear component.…”
Section: Discussionsupporting
confidence: 84%
“…Two early studies suggested that extinction under the influence of amobarbital (Barry, Etheredge, & Miller, 1965) and phenobarbital (Bindra, Nyman, & Wise, 1965) might not transfer to the undrugged state: Groups that received extinction with the drug responded more during a final, undrugged test than groups that had received extinction with a placebo. Similar results have been reported with alcohol (Cunningham, 1979), chlordiazepoxide (Delamater & Treit, 1988; Goldman, 1977; Kamano, 1972; Taub et al, 1977), and diazepam (Gorman, Dyak, & Reid, 1979). In nearly all of these experiments, however, the placebo controls never received exposure to the drug; it is therefore not clear that responding during testing was due to the drug’s specific combination with extinction (but see Cunningham, 1979, Experiment 2).…”
supporting
confidence: 87%
“…Cunningham alone showed that extinction performance could be reinstated by reintroducing the drug, a clear indication that extinction had been learned and could be cued by the drug state. In other experiments, no data were reported to indicate that extinction was ever learned under the drug (Goldman, 1977; Gorman et al, 1979; Kamano, 1972; Taub et al, 1977). And although other experiments did report a decline in responding during drug extinction (Barry et al, 1965; Bindra et al, 1965), the fact that extinction occurred in a single session in these experiments leaves open the possibility that the drug prevented memory consolidation afterward (but see Delamater & Treit, 1988).…”
mentioning
confidence: 94%
“…Will diazepam facilitate the process of learning that a stimulus or situation is harmless under such conditions, or will it retard this process? Most animal studies examining this question have used some type of conditioned avoidance paradigm and have generally concluded that benzodiazepines will either have no effect on the extinction process or will retard it (Gorman, Dyak, & Reid, 1979;Kamano, 1972;Thyer, Baum, & Reid, 1988). Experiment 3 was designed to address this question in the context of the present paradigm.…”
Section: Methodsmentioning
confidence: 99%